The seventh Libyan Diabetes and Endocrinology Conference (LDEC2009), April 7-9, 2009, Tripoli, Libya - Salhin, Amna; Besheya, Tawfek; Beshyah, Salem (Ibnosina Journal of Medicine and Biomedical Sciences, 2009)
The Libyan Association for Diabetes and Endocrinology (LADE) held its annual conference LDEC2009 over three days on April 7-9, 2009, in Tripoli. This was the seventh in the series of Libyan diabetes and endocrine conferences. It was the fourth conference held in the extended three-day format. The program targeted consultants and specialists in diabetes and endocrinology as well as other branches of general internal medicine who practice in hospitals and polyclinics. It included many primary health care providers. The conference seems to be emerging as the key “national” event in Libyan diabetes and endocrine circles. Many delegates attended from various parts of the country. Some delegates came for the first time from Sebha, Zliten, and Sirte. The representatives of the National Ministry of Health and The Libyan Board for Medical Specialties also acknowledged its status in their introductions during the opening ceremony. LDEC2009 had more satellite events than previous conferences the festival nearly an entire week. Two of these were outside Tripoli for the first time. “Sebha Diabetes Review 2009” was held jointly by the LADE and the Faculty of Medicine, University of Sebha. The “Zawia Diabetes Review 2009” was jointly organized by LADE and the Faculty of Medicine, 7th April University, Zawia. We received comprehensive press coverage throughout the three days. Unique new features included international speakers, the LADE Clinical debate, attendance by Libyan physicians in training from the UK and Italy, and notably that it was officially held under the auspices of LADE and included its AGM with a healthy and transparent discussion as well as accountability of the board to the General Assembly.